Recent advances in atomic resolution three-dimensional holography - Hiroshi Daimon; Tomohiro Matsushita; Fumihiko Matsui; Koichi Hayashi; Yusuke Wakabayashi (Advances in Physics: X)
Three-dimensional (3D) local atomic structure around specific functional atom plays a crucial role in functional materials, but it has not been able to be analyzed by a standard structure analysis method of x-ray diffraction (XRD) because this kind of small amount of atom has no translational symmetry. Recently several atomic-resolution holography methods have been developed, which can directly display the 3D atomic structure around this kind of specific atoms with no translational symmetry. These are the ‘photoelectron holography’, ‘x-ray fluorescence holography’, and ‘CTR holography’. Their accuracy improved dramatically by the development of new analysis codes and sensitive analyzers and detectors. A new technique of direct 3D atomic structure analysis method ‘stereography of atomic arrangement’ has also been developed. These techniques received renewed attention recently, and a project ‘3D Active-Site Science’ of JSPS Grant-in-Aid for Scientific Research on Innovative Areas has been pursued for 5 years. This article reviews principles and some results of atomic-resolution holography methods.